Factors Affecting Inpatient Patient Satisfaction of Social Security Agency of Health (BPJS) Participants at Bangkinang Hospital - Mahmudah; Hetty Ismainar; Budi Hartono; Doni Jepisah (Institute of Computer Science (IOCS), 2022)
Bangkinang Hospital is the main referral hospital for the people of Kampar, especially Social Security Agency of Health (BPJS) patients. Inpatient satisfaction at Bangkinang Hospital in 2021 is 76%. The standard according to the Ministry of Health is ≥90%. The BOR value has decreased in the last three years, namely 2019 by 57%, 2020 by 52% and 2021 by 43%. One of the causes is the Covid-19 pandemic that has occurred in the last two years. The standard BOR value is 60-85%. The purpose of this study was to look at the factors that influence inpatient satisfaction of Social Security Agency of Health (BPJS) participants at Bangkinang Hospital. The research was conducted in the inpatient room of Bangkinang Hospital, August 2022 with a total sample of 96. This type of research is an analytic study with a cross-sectional design. The data analysis used was univariate, bivariate and multivariate. Bivariate analysis showed that the variables that influenced patient satisfaction were empathy (p = 0.011), responsiveness (p = 0.009), reliability (p = 0.014) and patient experience (p = 0.007). Variables that have no effect are assurance (p = 0.238) and tangible (p = 0.073). Multivariate analysis obtained two confounding variables, namely assurance and tangible. The variable that has the dominant influence is the patient's experience with a POR value of 7,495. The conclusion of this study is that there are four variables that influence patient satisfaction and two confounding variables. The suggestion of this research is that it is necessary for homes to complete facilities in inpatient rooms, especially call bells, provide training to improve the competence of officers, and ESQ training.